Work Stress toward Work Environment, Management Support, and Employee Satisfaction among Employees of Public Organizations - Desa, Nasina Mat; Teoh, Lay Khoon; Asaari, Muhammad Hasmi Abu Hassan (AESS Publications, 2018)
Work stress has been rampant among employees in most organizations. Moreover, work stress could impact employees’ work life and organization performance. Unfortunately, employees of the public organization also are not exempted from experiencing work stress. The objectives of this paper are to understand the relationship between work stress toward work environment, management support, and work satisfaction; and also to determine the impact of work stress on work environment, management support, and work satisfaction among employees in the public organizations. Questionnaires were distributed among employees in the public organizations in consideration of the tools by various scholars on work stress, work environment, management support, and employee satisfaction. The paper had a response rate of 75.7% from the participation by those employees. Data analyses were done using SPSS specifically on correlation and regression. Results indicated that work stress had no impact on work environment, management support, and employee satisfaction. On the other hand, work environment had a positive relationship toward management support and employee satisfaction. Meanwhile, management support and employee satisfaction had a positive relationship. Finally, the public organizations’ top management could learn that work stress had an impacted on their employees’ work environment which subsequently will affect organizations’ performance